English modernism, national identity and the Germans, 1890-1950 - Rau, Petra (Nineteenth Century Series., 2009)
This is the first systematic analysis of the relationship between representations of 'Germanness' in modernist British literature, the construction of English identity and the negotiation of modernity. Major figures such as Conrad, Woolf and Ford are examined alongside popular or less-familiar writers such as Saki and Stevie Smith. Rau's book will be invaluable to scholars and will serve undergraduates working in modernism, literary history, and European cultural relations.